2005
DOI: 10.1002/ange.200501506
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrene‐Labeled G‐Quadruplex Oligonucleotide as a Fluorescent Probe for Potassium Ion Detection in Biological Applications

Abstract: Ionensonde: Ein Kalium‐empfindliches Oligonucleotid mit terminalen Pyreneinheiten kann als Fluoreszenzsonde für die Verfolgung der extrazellulären Konzentration von K+‐Ionen in Echtzeit unter physiologischen Bedingungen genutzt werden. Die Intensität der Excimer‐Emission (b) der gebildeten stuhlförmigen Quadruplexstruktur hängt von der K+‐Ionenkonzentration (0–200 mM) ab und unterscheidet sich deutlich von der ohne Kalium gemessenen Intensität (a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 25 publications
0
65
0
1
Order By: Relevance
“…[10,15] Interestingly, upon addition of K + , negative and positive peaks appeared (490 and 560 nm respectively) that corresponded to the FAM and TAMRA dyes, respectively. Human A C H T U N G T R E N N U N G telomere tetraplexes carrying FAM and TAMRA dyes described in previous papers exhibited a similar peculiarity, [3,8,20] which was attributed to the interactions between FAM and TAMRA dyes after forming the tetraplex structure.…”
Section: Spectra Of Fat-0mentioning
confidence: 99%
See 1 more Smart Citation
“…[10,15] Interestingly, upon addition of K + , negative and positive peaks appeared (490 and 560 nm respectively) that corresponded to the FAM and TAMRA dyes, respectively. Human A C H T U N G T R E N N U N G telomere tetraplexes carrying FAM and TAMRA dyes described in previous papers exhibited a similar peculiarity, [3,8,20] which was attributed to the interactions between FAM and TAMRA dyes after forming the tetraplex structure.…”
Section: Spectra Of Fat-0mentioning
confidence: 99%
“…[8,9] In a subsequent fluorescent probe (PSO-py), we exploited pyrene excimer emission for the transduction of the cation binding by the 15-mer thrombin-binding aptamer (TBA; d(GGTTGGTGTGGTTGG)). [10] Unlike in the FRET approach, stacking interactions between fluorophores (pyrene) were advantageous and produced efficient excimer emission. Due to the orientation of pyrene rings the PSO-py/K + complex emitted excimer fluorescence, while the random-coil structure of PSO-py in the absence of K + gave only monomer emission.…”
Section: Introductionmentioning
confidence: 99%
“…For Na + , Ca 2+ , Mg 2+ and NH4 + ions, the changes of relative excimer-emission intensities were very weak due to their weak binding affinity with thrombin-binding aptamer. 8,31 Hence, the proposed method represents good specificity for K + ions over Na + , Mg 2+ , Ca 2+ , and NH4 + ions at experimental condition. K + ions coexist with an excess of Na + ions in extracellular conditions.…”
Section: The Sensitivity and Specificity For Detecting Target K + Ionsmentioning
confidence: 88%
“…[5][6][7] In 2005, Nagatoishi et al reported thrombin-binding aptamer labeled by pyrene moieties at both ends for the detection of potassium in the presence of an excess of Na + . 8 However, these methods were greatly limited in their applicability because modified aptamers may cause reduction of affinity and specificity. [9][10][11][12] Recently, Shi et al reported an aptamer-based optical biosensor for K + detection, in which aptamer was unmodified as the molecular recognition element.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that there is no clear isoemissive point at around 640 nm because it is a more complex system than the simple two-component excimermonomer equilibrium. 43 Maximum I M /I E value was observed aer 180 min of enzymatic reaction (Fig. 3b).…”
Section: Supramolecular Assemblies Triggering the Development Of Achementioning
confidence: 97%